The Replacement of The Elected Members of House of Representative in Open List Proportional General Election - Khalid Dahlan (Syiah Kuala Law Journal, 2021)
The filling of replacements for elected members of the House of Representative who no longer meet the requirements at the time of election with a candidate who has a lower vote than other candidates by the party is contrary to the open list proportional electoral system. This study describes the process of changing candidates who no longer meet the requirements at the time of voting in terms of the applied electoral system. The research method uses normative juridical research. The determination of the elected candidates for the House of Representative members in an open list proportional system is determined by the majority of the votes acquired by the candidates. The vote of a candidate who no longer meets the requirements to become the valid vote of a political party, in an open list proportional electoral system, the party should cast the vote to the candidate who has the next most votes to gain a seat in the parliament. Parties as participants in the elections for the House of Representatives do not have the discretionary power to transfer their votes to candidates who have lower votes than other candidates because they are against the morals and ideals to be achieved in the application of an open list proportional electoral system.